The - Nina Baym; general editor; Robert S. Levine; associate general editor (W.W. Norton & Company, 2013)
The Norton Anthology of American Literature, Shorter Eighth Edition, features a diverse and balanced variety of works and thorough but judicious editorial apparatus throughout. The new edition, which also newly includes much-requested authors and selections and 130 in-text images, remains an unmatched value for students